Pauvreté, durabilité et capacités de choix : Les paysans centrafricains peuvent-ils éviter le cercle vicieux ? - Benoît Lallau (Développement Durable et Territoires)
This article explores the relationship between poverty and sustainability. The study is based upon qualitative research conducted in CAR and a conceptual framework that emphasizes individuals' choice capabilities. These capabilities are limited by low endowment in capital (financial, physical, natural, human, and social), and by the lack of opportunities (imperfect markets, government failure, lack of development funds). Consequently, individuals tend to favor a short term risk management strategy which leads to non sustainability. This strategy impacts not only ecosystems, but also economic integration, social cohesion and human development. Poverty and non sustainability reinforce each other, illustrating a cumulative causation process.